Étude Quantitative des polyphénols des extraits des graines de deux plantes médicinales : Fenouil (Feoniculum vulgare Mill) et cubebe (Piper cubeba) et l’évalution de l’activité biologique - ZOUINI, Rania; NEHARI, Ikram (My University, 2024)
Medicinal plants have been used for thousands of years for their therapeutic properties, and modern research continues to explore their potential to develop new treatments. Essential oils and plant extracts are a valuable source of bioactive compounds with antioxidant and antibacterial properties. The aim of our work was to study the biological and biochemical activity of essential oils and seed extracts from fennel (Foeniculum vulgare Mill) and cubeba (Piper cubeba) plants. Steam distillation was used to extract the essential oils, while the extracts were obtained by macerating the plant powder in distilled water for 24 hours. Oil yields were 1.02% for Fennel and 0.97% for Cubeb, while extract yields were 9.8% for Fennel and 8.7% for Cubeb. Total polyphenol levels (using the Folin-Ciocalteu method) were 80 mg EQAG/g for Cubeb and 12 mg EQAG/g for Fennel. Quantitative estimates of flavonoids (using the aluminium trichloride method) were similar between the two plants, with 165 mg/g EQ for Cubeb and 185 mg/g EQ for Fennel. The antioxidant activity of the various extracts (aqueous extract and essential oils) was assessed using the DPPH free radical scavenging method. The IC50 values for the oils were 45 mg/ml for Fennel and 0.029 mg/ml for Cubeb, while for the extracts they were 7.4 mg/ml for Fennel and 0.3 mg/ml for Cubeb. With regard to the antibacterial activity of EOs, disc diffusion tests showed that Fennel and Cubeba seed oils inhibited the growth of seven types of bacteria and yeasts, with Cubeba oil being particularly effective against C. albicans, E. coli and P. mirabilis. Fennel oil showed stronger inhibition against Bacillus cereus. The oils also demonstrated bactericidal activity with concentrations ranging from 0.02% to 1.25% for Cubebe and from 1.25% to 5% for Fennel. The extracts also showed significant antibacterial activity using the well diffusion method, with cubeb being more effective against P. aeruginosa , P. mirabilis , while fennel was more effective against Bacillus cereus and Staphylococcus aureus. The extracts demonstrated bacteriostatic activity with effective concentrations ranging from 0.37 mg/ml to 6.25 mg/ml for both plants.
Keywords: essential oil; antibacterial activity; antioxidant activity; flavonoid; polyphenol; Piper cubeba; Foeniculum vulgare Mill